Psychobiology and candidate endophenotypes in psychopathy (2011)
At present there exist a lot of neurobiological and molecular studies that suggest genetic susceptibility to different characteristics of the expression of psychopathy; nevertheless, so far much of those results have not successfully and consistently been replicated, mainly because of the difficulties in: sensitivity, specificity and validity of the clinical evaluation methods; the size and type of the chosen population; and the experimental designs used. Unfortunately, the diagnoses in psychiatry and psychology uses a classification based on prevalence and intensity of the symptoms and do not taken into account the etiology, neurobiology, epidemiology, genetics and response to medication. The use of limited diagnostic tools analysis and dichotomized the clinical diagnoses lead to a loss of power in the validation of the phenotype being studied and the lack of neurobiological knowledge of the molecules implicated in this kind of disorders, increasing the genetic heterogeneity. This condition obstructs the mapping of susceptibility genes which might outline the neurobiology and pathophysiology of the disease as a central scheme in the conceptualization of the syndrome. This article, we present the most appropriate strategies for examining the phenotype of psychopathy through the use of endophenotypes